FEATURES OF THE INTERNAL PATTERN OF THE DEFECT IN CHILDREN OF PRIMARY SCHOOL AGE WITH VISUAL IMPAIRMENT - Adeeva, Tatiana; Tikhonova, Inna; Khazova, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Ideas about the internal defect pattern are studied in this article. The internal pattern of a defect is a set of ideas and feelings of a person about the defect. It is a mechanism of personality development and a factor of adaptation or disadaptation of the personality. Studies of the internal pattern of the defect in modern clinical and special psychology are episodic. In modern studies, attention is paid to a greater extent to the study of the specifics of the emotional, relational component, other components of the internal pattern of the defect are not sufficiently studied. However, they are of great importance for the formation of the internal defect pattern and I-concept as a whole.The analysis of the results of the study of the Self-concept of primary school children with visual impairment is presented in the article. Features of the main components of the internal picture of the defect are presented in the work. Specific features of cognitive, physical, emotional components are established in the course of research. Contradictions are revealed in cognitive and physical components. Two types of emotional response to the defect were found in children: ignoring and compensatory. The motivational sphere of children with severe visual impairment is affected by the defect. The relationship between the specifics of the components of the internal pattern of the defect and the features of the formation of the Self-concept is assumed.